Predictive Maintenance and Predictive Repair of Road Vehicles—Opportunities, Limitations and Practical Applications - Jozsef Nagy; Istvan Lakatos (Engineering Proceedings)
With drastic increases in the complexity of road vehicles, increasing environmental and cost pressures have led to the obsolescence of previous fixed-schedule maintenance systems. The aerospace industry, following the road vehicle industry, is also beginning to use the predictive maintenance method increasingly widely. A possible next step for critical breakdowns could be a predictive service. While preventive maintenance is able to be used more frequently, the possibility of preventive repair is also limited to the fault symptoms, and is unsuitable for preventing fast-running breakdowns. Due to the current state of technological development in this area, it will take a few more years for lower-priced cars to catch up to the sensor and data structures of current premium-series vehicles, such that the mass use of these methods in road vehicles can become widespread.